Proposals for the Operationalisation of the Discourse Theory of Laclau and Mouffe Using a Triangulation of Lexicometrical and Interpretative Methods - Glasze, Georg (Forum Qualitative Sozialforschung / Forum: Qualitative Social Research, 2007)
The discourse theory of Ernesto LACLAU and Chantal MOUFFE brings together three elements: the FOUCAULTian notion of discourse, the (post-) MARXist notion of hegemony, and the poststructuralist writings of Jacques DERRIDA and Roland BARTHES. Discourses are regarded as temporary fixations of differential relations. Meaning, i.e. any social "objectivity", is conceptualised as an effect of such a fixation. The discussion on an appropriate operationalisation of such a discourse theory is just beginning. In this paper, it is argued that a triangulation of two linguistic methods is appropriate to reveal temporary fixations: by means of corpus-driven lexicometric procedures as well as by the analysis of narrative patterns, the regularities of the linkage of elements can be analysed (for example, in diachronic comparisons). The example of a geographic research project shows how, in so doing, the historically contingent constitution of an international community and "world region" can be analysed.URN: urn:nbn:de:0114-fqs0702143